Aplikasi Produk Radar C-Band dalam Identifikasi Awan Penghasil Hujan Es (Studi Kasus: Bogor, 24 Januari 2022) - Sulistiyono, Wahyu; Salsabil, Nadhilah Humairah Salwa; Ramadhan, Shandy Alhaq (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2024)
The study on the development and convective weather conditions in Bogor, Indonesia, was conducted on January 24, 2022. The research aimed to understand the process of development and convective weather conditions using a data radar system. The Bogor area was surveyed using the Tangerang Radar with a 50-km radius. The study used quantitative research based on the Radar Cuaca data and collected data from CMAX, VIL, and Zhail data from the Gematronik Raw Data radar to understand the weather conditions and wind conditions. The results showed that the development and convective weather conditions were observed at 06.03 UTC with a maximum reflektifitas of 40-45 dBz, reaching peak at 06.35 UTC with a maximum reflektifitas of 56.5 dBz. The wind conditions were observed at 08.19 UTC with reflektivity values below 40-45 dBz. The highest wind speed was identified at 06.35 UTC with a 76.77% probability, similar to the CMAX product.